The Effect Of Lavender Aromatherapy On Post Sectio Caesaria Pain Intensityat The Grandmed Hospital Lubuk Pakam - Titin Novayanti Dey; Siti Khadijah Pasaribu; Wilda Wahyuni Siregar (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Sectio caesarea is a method of artificial delivery to give birth to a fetus by means of surgery and an incision in the uterine wall through the outer skin of the mother's abdomen. This caesarean section can cause pain in the mother and changes in tissue continuity can occur. According to the World Health Organization (WHO), the standard for births carried out using the caesarean section (SC) method is around 5-15% per 1000 births in the world. the average incidence rate in government hospitals is 11% and 30% in private hospitals. There are two ways to overcome pain, namely pharmacological and non-pharmacological, to overcome pain using pharmacological methods, this can be done by administering analgesic drugs and to overcome pain using non-pharmacological methods, this can be done by providing aromatherapy to reduce the pain. This research aims to determine the effect of aromatherapy on pain after caesarean section at Grandmed Lubuk Pakam Hospital. To determine the effect of aromatherapy on pain after caesarean section at Grandmed Lubuk Pakam Hospital. Based on statistical tests with the help of SPSS based on the Paired Sample T-test statistical test, a value of 0.000 was obtained, which means there is an influence of lavender aroma therapy on the intensity of post caesarean section pain at Grand Med Lubuk Pakam Hospital.